Comparative susceptibility of larval instars and pupae of the western corn rootworm to infection by three entomopathogenic nematodes - Kurtz, B.; Hiltpold, Ivan; Turlings, Ted; Kuhlmann, Ulrich; Toepfer, Stefan (My University, 2009)
As a first step towards the development of an ecologically rational control strategy against western corn rootworm (WCR; Diabrotica virgifera virgifera LeConte, Coleoptera: Chrysomelidae) in Europe, we compared the susceptibility of the soil living larvae and pupae of this maize pest to infection by three entomopathogenic nematode (EPN) species. In laboratory assays using sand-filled trays, Heterorhabditis bacteriophora Poinar and H. megidis Poinar, Jackson & Klein (both Rhabditida: Heterorhabditidae) caused comparable mortality among all three larval instars and pupae of D. v. virgifera. In soil-filled trays, H. bacteriophora was slightly more effective against third larval instars and pupae, and H. megidis against third larval instars, compared to other developmental stages. In both sand and soil, Steinernema feltiae (Filipjev) (Rh.: Steinernematidae) was least effective against second instars. In conclusion, all larval instars of D. v. virgifera show susceptibility to infection by all three nematodes tested. It is predicted that early application against young larval instars would be most effective at preventing root feeding damage by D. v. virgifera. Applications of nematodes just before or during the time period when third instars are predominant in the field are likely to increase control efficacy. According to our laboratory assays, H. bacteriophora and H. megidis appear to be the most promising candidates for testing in the field.
Keywords: Diabrotica virgifera virgifera; Coleoptera; Chrysomelidae; Heterorhabditis bacteriophora; Heterorhabditis megidis; Steinernema feltiae